(untitled) (The Review of Diabetic Studies, 2025)
Background: Hypertension is a major public health challenge and a leading risk factor for cardiovascular morbidity and mortality, particularly in rural India where lifestyle modification awareness and practices are often inadequate. Non-pharmacological interventions such as meditation, yoga, physical exercise, and dietary regulation play a crucial role in blood pressure control. Objective: To evaluate the effectiveness of the MEDY approach (Meditation, Exercise, Diet, and Yoga) on knowledge and practice regarding lifestyle modification among hypertensive patients in a selected rural area of Nandod Taluka, Narmada district, Gujarat. Methodology: A true experimental pre-test and post-test control group design was adopted. The pilot study included 40 hypertensive patients (20 experimental and 20 control) selected using systematic random sampling. The experimental group received the MEDY intervention for four weeks, while the control group received routine care. Knowledge and practice were assessed using structured questionnaires. Results: The experimental group showed a statistically significant improvement in both knowledge and practice scores after the MEDY intervention (p < 0.05), whereas no significant change was observed in the control group. Conclusion: The MEDY approach is an effective, feasible, and culturally acceptable lifestyle intervention for improving knowledge and practice related to hypertension management in rural settings.